2010
DOI: 10.1089/end.2009.0219
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Laparoscopic Nephrectomy Simulator Is Lacking in Construct Validity

Abstract: The LN-VR simulator did not distinguish between intermediate and experienced participants. The analysis of the learning curves suggests that the tasks measured dexterity in using the simulator rather than an actual improvement of operative skills. We conclude that the LN-VR simulator does not have sufficient construct validity and is therefore, in its present form, not suitable for implementation in a urologic training program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…The lack of construct validity for virtual reality motion metrics was surprising as virtual reality models are highly validated training tools and the motion metrics also have shown construct validity for assessment . However, previous validation studies of the virtual reality trainer used in this study have shown conflicting results . Eriksen and Duffy et al demonstrated construct validity in virtual reality using eight different tasks, and all metrics showed significant difference between the experienced and inexperienced group.…”
Section: Discussionmentioning
confidence: 70%
“…The lack of construct validity for virtual reality motion metrics was surprising as virtual reality models are highly validated training tools and the motion metrics also have shown construct validity for assessment . However, previous validation studies of the virtual reality trainer used in this study have shown conflicting results . Eriksen and Duffy et al demonstrated construct validity in virtual reality using eight different tasks, and all metrics showed significant difference between the experienced and inexperienced group.…”
Section: Discussionmentioning
confidence: 70%
“…Various laparoscopic surgery training systems have been developed. Some recent systems reproduces the entire procedure of laparoscopic radical nephrectomy [18,19]. However, to the best of our knowledge, no other system provides an actual operative view of the individual patient.…”
Section: Discussionmentioning
confidence: 99%
“…An international consent must also be defined in order to uniform the training and assessment techniques (21). Recently, The European Endoscopic Surgery Consensus recommended that the basic laparoscopic surgical tasks should be practiced in a laboratory before the practice on human beings (22).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, The European Endoscopic Surgery Consensus recommended that the basic laparoscopic surgical tasks should be practiced in a laboratory before the practice on human beings (22). But, although modern simulators are more realistic, it is still hard to transfer the virtual reality skills to surgical practice (21,23,24). LapSim simulators have programs very similar to real surgery, and may be considered an advantageous factor.…”
Section: Discussionmentioning
confidence: 99%